2018
DOI: 10.1016/j.jhydrol.2017.10.073
|View full text |Cite
|
Sign up to set email alerts
|

Soil seal development under simulated rainfall: Structural, physical and hydrological dynamics

Abstract: HighlightsX-ray CT was effectively used to quantify soil seal/crust thickness.Different micro-morphological zones within seal layers were revealed.Rainfall had a strong and rapid impact on water transport and retention in soil.The existence of a soil-dependent raindrop impact threshold was hypothesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 60 publications
6
65
0
2
Order By: Relevance
“…This explanation is in accordance with Armenise et al [15] who investigated influence of rainfall in the hydraulic conductivity and found two different trends in soil porosity vs. depth. Moreover, high rainfall may result in leaching and washing of salts from the top soil to deeper depths.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This explanation is in accordance with Armenise et al [15] who investigated influence of rainfall in the hydraulic conductivity and found two different trends in soil porosity vs. depth. Moreover, high rainfall may result in leaching and washing of salts from the top soil to deeper depths.…”
Section: Discussionsupporting
confidence: 92%
“…So far, hydraulic conductivity in soil is directly connected with particles size distribution in soil profile. Several methods have been tested for determination of hydraulic conductivity; this included integrated global soil databases with land use/land cover databases and saturated hydraulic conductivity [13], pedotransfer functions [14], rainfall-induced seals [15] and influence of biochar [16]. These investigations provided valuable information that was applied in agricultural soils around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Similar trends were observed in previous studies, but usually due to the surface clogging or because lower suction pressure was applied during the infiltration [59]. Decreasing unsaturated hydraulic conductivity through the growing season has been reported as well due to clogging of pores by fine soil particles detached from aggregates by rainfall impact [36] or rainfall induced soil surface sealing [60]. The reason for the different outcome in our case is not clear; however, a possible explanation could lie in the specific weather conditions in 2015, which resulted in exceptionally dry topsoil conditions before the spring tillage and throughout the season.…”
Section: Tension Infiltration Experimentssupporting
confidence: 85%
“…The reduction in water infiltration produces a reduction in total water accumulated in the soil. Although it has been indicated that soil surface sealing may improve soil moisture temporal stability (Sela et al, ), seal formation has a strong impact in the overall ability of soil to function as water reservoir (Armenise et al, ). This fact may have important impacts not only on rainfed agriculture, due to the loss of effective rainfall, but also under irrigation, because the application of water can favour the formation of seals and reduce water infiltration into the soil.…”
Section: Introductionmentioning
confidence: 99%